Applied Geochemistry with Case Studies on Geological Formations, Exploration Techniques and Environmental Issues - Felipe Mazadiego, Luis; De Miguel Garcia, Eduardo; Barrio-Parra, Fernando; Izquierdo-Díaz, Miguel (IntechOpen, 2020)
Geochemistry has become an essential subject to understand our origins and face the challenges that humanity will meet in the near future. This book presents several studies that have geochemistry as their central theme, from the description of different geological formations, through its use for the characterization of contaminated sites and their possible impact on ecosystems and human health, as well as the importance of geochemical techniques as a complement to other current scientific disciplines. Through the different chapters, the reader will be able to approach the world of geochemistry in several of its subfields (e.g. environmental, isotope, or biogeochemistry) and learn through practical cases.